The Effect of Digital Literacy on Students’ Self-Disclosure in Online Counseling Sessions - Ledyva Yolanda; Ari Prasetyoaji (Universitas Teknologi Yogyakarta, 2026)
Study aims to empirically examine the influence of digital literacy on the self-disclosure of Generation Z college students during online counseling sessions. Using a quantitative approach with a causal associative method, data were collected from 2,134 active students in Indonesia. The findings indicate that digital literacy has a significant positive impact on self-disclosure. Although students exhibit exceptionally high technical digital skills, a critical gap exists in digital safety literacy, which triggers a